Knowledge and Practice of Present and Future Dentists about Nutrition Counseling in Yazd, Iran in 2022 - Fahimeh Rashidi Maybodi; Zahra Falahati Marvasti; Azadeh Nadjarzadeh (Shahid Sadoughi University of Medical Sciences, 2023)
Background: Inadequate nutrition can affect oral health. Compromised oral health can also alter food choices and negatively lead to poor nutrition. This study aims to assess the knowledge and practice of dentists and dental students regarding nutrition counseling. Methods: In this cross-sectional study, a valid and reliable four-part questionnaire was conducted among senior students and dentists in Yazd city in February 2022. All 40 senior students in the Faculty of Dentistry were selected by census method, and 98 dentists were selected randomly from all the names registered in the system of Medical Council. Data were analyzed by SPSS version 25 and t-test and Chi-square tests were used (P-value < 0.05) Results: Out of a score 9, the mean score of knowledge was 7.12 ± 1.75 for dentists and 6.48 ± 1.2 for students. The mean score of dentists was higher than students (P = 0.03). Out of a score of 10, the mean score of dentists and students' practice were 3.26 ± 2.43 and 3.20 ± 1.82, respectively. There was no significant difference regarding the mean score practice in two groups (P = 0.879). Conclusions:  The knowledge level of both groups was not good but acceptable, and the quality of practice in both groups was poor. It seems that there is a need for corrective educational interventions to improve the practice of dentists and dental students.